Morphological Abnormalities of the Thalamus in Youths With Attention Deficit Hyperactivity Disorder - Ivanov, Iliyan (Am J Psychiatry, 2010)
OBJECTIVE: The role of the thalamus in the genesis of attention deficit hyperactivity disorder (ADHD) remains poorly understood. The authors used anatomical MRI to examine the morphology of the thalamus in youths with ADHD and healthy comparison youths. METHOD: The authors examined 46 youths with ADHD and 59 comparison youths 8–18 years of age in a cross-sectional case-control study. Conventional volumes and measures of surface morphology of the thalamus served as the main outcome measures. RESULTS: A mixed-effects model comparing whole thalamic volumes revealed no significant differences between groups. Maps of the thalamic surface revealed significantly smaller regional volumes bilaterally in the pulvinar in youths with ADHD relative to comparison subjects. Post hoc analyses showed that ADHD patients who received stimulants (N=31) had larger conventional thalamic volumes than untreated youths with ADHD, and maps of the thalamic surface showed enlargement over the pulvinar in those receiving stimulants. Smaller regional volumes in the right lateral and left posterior thalamic surfaces were associated with more severe hyperactivity symptoms, whereas larger regional volumes in the right medial thalamic surfaces were associated with more severe symptoms of inattention. CONCLUSION: These findings demonstrate reduced pulvinar volumes in youths with ADHD and indicate that this same area is relatively enlarged in patients treated with stimulants compared to those untreated. Associations of hyperactivity scores with smaller regional volumes on the lateral thalamic surface and inattention scores with larger regional volumes on the medial thalamic surface suggest the differential involvement of thalamic subcircuits in the pathogenesis of differing ADHD symptoms.